The influence of managerial ownership on bank market value, performance, and risk: evidence from banks listed on the stoxx global index - Gulamhussen, M. A.; Pinheiro, C.; Sousa, R. (Journal of International Financial Management and Accounting, 2012)
We follow agency theory to assess the influence of managerial ownership on the market value, performance, and risk of 123 listed banks in 23 countries included in the STOXX Global Index in 2007 and 2010. After controlling for bank characteristics, regulatory restrictions, and macroeconomic conditions, our findings show a positive relation between managerial ownership and both market value (Tobin's Q) and performance (ROA and ROE). Moreover, we find a negative relation between managerial ownership and risk (EDF, NPL/L, and Z-SCORE). Bank market value and performance is a non-linear, inverse U-shaped function of managerial ownership. The negative relation between managerial ownership and bank risk is also non-linear and U-shaped. Our results remain robust to reverse causality. In their effort to immunize the global financial system from systemic risks, central banks and practitioners should find our results relevant for regulation purposes.